A comprehensive strategy for perioperative care of pancreaticoduodenectomy according to the risk stratification by pancreatic fistula and delayed gastric emptying - Yoshifumi Morita; Takanori Sakaguchi; Shinya Ida; Ryuta Muraki; Ryo Kitajima; Satoru Furuhashi; Makoto Takeda; Hirotoshi Kikuchi; Yoshihiro Hiramatsu; Hiroya Takeuchi (Asian Journal of Surgery, 2022)
Background/Objective: Pancreaticoduodenectomy (PD) is highly invasive with unsatisfactory postoperative complication rates. Nutritional and fluid management after major surgery attracts much attention with regard to the reduction in severe postoperative complications. We retrospectively analyzed PD cases and proposed a novel strategy for perioperative fluid and nutritional therapy according to the risk stratification by pancreatic fistula (PF) and delayed gastric emptying (DGE). Methods: Between 2003 and 2018, 140 patients underwent PD at our institute of which 134 patients were enrolled. We evaluated the clinicopathological factors affecting severe (≥10%) body weight loss (BWL), factors affecting the incidence of PF and intraabdominal complications (IAC), and factors related to DGE. Results: Multivariate analysis indicated that male sex, severe PF, and DGE are significant risk factors for BWL ≥10%. PF and IAC were predominantly observed in male patients and those with non-pancreatic cancer. A fluid balance ≥6000 ml on postoperative day 2 was the sole risk factor for primary DGE. Secondary DGE significantly correlated with stomach preserving PD. Importantly, the average BWL was around 15% in grade B or C secondary DGE. Conclusion: Severe postoperative complications resulted in significant BWL. Enteral feeding is unnecessary in cases with a hard pancreas and dilated pancreatic duct if appropriate perioperative fluid management is performed. Secondary DGE followed by PF or IAC is unavoidable to some extent, especially in the case of soft pancreas with a fine pancreatic duct. In such cases, enteral feeding with tube ileostomy should be considered, and stomach preserving PD is likely to be harmful.